Surgical techniques in total knee arthroplasty (TKA) and alternative procedures - Affatato, Saverio (Woodhead Publishing series in biomaterials ;, 2015)
Total knee arthroplasty (TKA) is commonly considered to be a reliable procedure, with high implant survival rates at 10 to 15 years of follow-up. The goal of total knee replacement surgery is to relieve pain and obtain better knee function. This is achieved by ensuring correct patient selection, pre-operative deformity, implant design and accurate surgical techniques. This book covers a range of techniques for the realisation of functional joint motion and stability. The first part of the book will describe fundamentals in total knee arthroplasty and alternative procedures. The second half will look at surgical techniques and considerations whilst the final chapters will address future trends and challenges in the field of knee surgery. This book will be an essential reference for academics, orthopaedic surgeons, and those training in medicine, physiatry and rheumatology.